The Effect Of Good Corporate Governance Towards Company Financial Performance - Agustina, Dwi; Ardiansari, Anindya (Management Analysis Journal, 2019)
The aims of this study were to describe and analyze the effect of good corporate governance on company financial performance. The population in this study was companies listed as participant of corporate governance perception index during the period 2010-2016. The sample in this research was 105 observations which consisted of 15 companies and observation through purposive sampling method which was based on certain criteria. Analysis technique which was used in this research was simple linear regression analysis with eviews 9 program. The results of this research indicated that good corporate governance had insignificant positive effect on company financial performance. The adjusted R Square value was 0.252689 showed the ability of good corporate governance variable to explain company financial performance that was 25.27% while the rest was 74.73% could be explained by other variables. 74.73% (100% -25.27%). The conclusion of this research is GCG variable has no significant effect on company financial performance. Suggestion for company management should maintain its rate on CGPI. For the investors before investing, investors should choose companies that have good CGPI ratings. For the next researcher should replace or add other research variables, such as capital structure and financial statements quality.